F. Marion Crawford papers - Crawford, F. Marion (Francis Marion), 1854-1909.; Crawford, F. Marion (Francis Marion), 1854-1909.
Fourteen letters written by Crawford to his uncle, Samuel Ward, 1881 May 11-1882 October 5, and a holograph draft (223 pages) of Crawford's novel, "An American Politician," dated August 16, 1884 in Constantinople.
Author.
Collection material in English.
Keywords: Ward, Samuel, -- 1814-1884.; Authors